Efficacy of pharmacological therapies for preventing post-dural puncture headaches in obstetric patients: a Bayesian network meta-analysis of randomized controlled trials - Ge Zhao; Guang Song; Jing Liu (BMC, 2023)
Abstract Background Post-dural puncture headache (PDPH) is a major complication of neuraxial anesthesia. PDPH usually occurs after Caesarean section in obstetric patients. The efficacy of prophylactic pharmacological therapies remains controversial. Methods Seven pharmacological therapies (aminophylline (AMP), dexamethasone, gabapentin/pregabalin (GBP/PGB), hydrocortisone, magnesium, ondansetron (OND), and propofol (PPF)), were studied in this Bayesian network meta-analysis. The primary outcome was the cumulative incidence of PDPH within 7 days. Secondary outcomes included the incidence of PDPH at 24 and 48 h postoperatively, the severity of headache in PDPH patients (24, 48, and 72 h postoperatively), and postoperative nausea and vomiting (PONV). Results Twenty-two randomized controlled trials with 4,921 pregnant women (2,723 parturients received prophylactic pharmacological therapies) were included. The analyses demonstrated that PPF, OND, and AMP were efficient in decreasing the cumulative incidence of PDPH during the follow-up period compared to the placebo group (OR = 0.19, 95% CI: 0.05 to 0.70; OR = 0.37, 95% CI: 0.16 to 0.87; OR = 0.40, 95% CI: 0.18 to 0.84, respectively). PPF and OND had the lower incidence of PONV compared to the placebo group (OR = 0.07, 95% CI: 0.01 to 0.30; and OR = 0.12, 95% CI: 0.02 to 0.63). No significant difference in other outcomes was found among different therapies. Conclusions Based on available data, PPF, OND, and AMP may have better efficacy in decreasing the incidence of PDPH compared to the placebo group. No significant side effects were revealed. Better-designed studies are requested to verify these conclusions.